Gender, social acceptability and the adoption of supermarkets: evidence from Libya - Sehib, K.; Jackson, Elizabeth; Gorton, M. (Wiley-Blackwell Publishing Ltd., 2013)
This paper explores factors affecting consumers' adoption of supermarkets in a nation whose retail environment has been dominated by traditional markets and small independent stores for generations. In-depth interviews with Libyan shoppers (n = 32) indicate that social acceptability is a major factor governing adoption of supermarkets. In Libya, food shopping has traditionally been a task for male household members, with markets regarded as inappropriate spaces for female alone or with other women. However, the safer, cleaner and less crowded environment offered by large supermarkets has contributed to women feeling more comfortable shopping for food, and henceforth being able to shop as independent consumers. This has been welcomed by both men and women; traditional culture, rather than constraining the spread of supermarkets, may act as a facilitator. For practitioners, a critical factor underpinning the development of supermarkets in Libya will be the degree to which they offer a more female-friendly and safer shopping experience than traditional retail outlets.